Questioning assent: how are children's views included as families make decisions about clinical trials?. (2nd May 2016) - Madden, L.; Shilling, V.; Woolfall, K.; Sowden, E.; Smyth, R. L.; Williamson, P. R.; Young, B.
Abstract : Background: Assent is used to take children's wishes into account when they are invited into clinical trials, but the concept has attracted considerable criticism. We investigated children's accounts of decision‐making with the aim of informing practice in supporting children when invited to join a clinical trial. Methods: We audio‐recorded qualitative, semi‐structured interviews with 22 children aged 8–16 years about being invited to take part in a clinical trial. Most children were interviewed with their parents. Analysis of the transcribed interviews examined the content of participants' accounts thematically, whilst also drawing on principles of discourse analysis, which examines how individuals use talk to achieve certain effects or social practices. Results: It was not possible to separate children's knowledge of the clinical trial, or their decision‐making processes from that of their parents, with parents taking a substantial mediating role in producing their children's decisions. Decision‐making gradually unfolded across time and events and was interwoven within the family context, rather than happening in one moment or in the clinical setting. Whilst children valued their parents' role, a case study of child–parent disagreement indicated how children can struggle to be heard. Conclusions: Decisions happen within a process of family dynamics, in contrast to ideas of assent that isolate it from this context. Parents have a substantial role in children's decisions, and thus how families come to provide consent. Reflecting this we argue that assent practices need to focus on supporting parents to support their children in learning and deliberating about trials. However, this needs to be accompanied by practitioners being alert to the possibility of divergence in child and parent views and enabling children's perspectives to be heard.